地方本位教育的探究教學增進物理科師資生 教師專業知能：以大學社會責任實踐偏鄉 教育為例 Inquiry-Based Teaching Approach to Improve Physics Preservice Teachers' Professional Competence: University Social Responsibility Project for Place-Based Education in Rural Areas - 林建隆 Jang-Long Lin; 林登敏 Deng-Min Lin; 鄭依萍 Yi-Ping Cheng; 康智凱 Zhi-Kai Kang (National Taiwan Normal University, 2023)
探究教學是當前自然科學領域課綱中強調的重要教學方法和特色，且被認為是可解決學習成效的通用方案，但針對偏鄉地區，師資生較缺乏結合當地文化與環境所需具備的教學技能和知識，若能融入地方本位教育特色於教師職前教育課程，才可更有效引導及激發偏鄉學生的潛能、提升自信，進而促其擁有自我實現的能力，此乃現今師資培育所面臨的重要問題。 本研究採混合研究法，以偏鄉國中為教學實踐場域，引導師資生體驗、設計及施行符合偏鄉地方本位特色的探究教學教材，探討其對職前師資培育課程的價值及整體師資生專業知能提升情形。研究對象為修習「物理科教學應用與實作」教程必修課程的15名師資生。研究工具採「教師專業知能量表」；質性部分針對教師反思日誌、教學活動錄影、錄音、師資生反思實踐心得、期末歷程檔案與晤談紀錄等進行資料分析。研究結果顯示，師資生於偏鄉場域實踐教學後，教師專業知能量表的習得、運用、重要程度及總量表之後測均顯著優於前測，師資生對設計與實踐偏鄉地方本位特色探究課程、小組合作學習、探究引導與提問技巧、主動關懷偏鄉教育的責任感等各方面表現亦均有所提升，本研究可供職前師資培育相關課程之參考。 According to the United Nations 2030 Sustainable Development Goals, rural education should fulfill the requirements of quality education and reduce inequality. The concept of "justice in education" should not be limited to resource allocation. Students in rural areas face several disadvantages. Teachers should consider the living conditions of students in rural areas to avoid exacerbating the challenges faced by these students, who often lack interest in education and feel powerless. Inquiry instruction is an important teaching method in the field of natural sciences that aims to improve learning effectiveness. However, in rural areas, preservice teachers often lack the necessary teaching skills and knowledge to integrate local culture and the environment into their teaching practices. If the characteristics of place-based education are integrated into preservice teacher training courses, preservice teachers can develop the ability to guide and stimulate rural students to unlock their potential, increase their confidence, and undergo self-realization. This has become crucial in preservice teacher training. Using a rural junior high school as the site of teaching practice, in this study, preservice teachers were guided to experience, design, and implement an inquiry-based teaching course that incorporated the characteristics of rural place-based education (PBE). The study explored the value of this approach in preservice teacher training courses and how it can enhance overall professional knowledge in preservice teachers. A review of the literature was conducted to investigate the effectiveness of a PBE teaching program for enhancing the professional development of teachers. According to the constructivist student-centered perspective in the literature, an innovative PBE inquiry teaching program was proposed. To effectively implement this program, teachers should be familiar with the characteristics of PBE in their field. Teachers should also be able to identify students' original ideas and ask PBE-related questions to increase students' learning motivation. Teachers should also guide students to perform inquiry-based activities, facilitating the exchange of ideas among students through communication and interaction. Students should be encouraged to assimilate, adjust, and construct new ideas through critical thinking under conflicting scenarios. Furthermore, students are expected to evaluate and apply these new ideas to new PBE scenarios provided by teachers. Finally, students should reflect on the evolution of their ideas, ultimately developing problem-solving skills in scientific learning and innovative thinking abilities while expanding their knowledge base. In this study, a remote junior high school in the mountainous area of central Taiwan was investigated using a mixed-method approach. Quantitative data were collected using questionnaires, and qualitative data were collected through other methods. The research participants were 15 preservice teachers taking a compulsory course titled Application and Practice of Physics Teaching. This course incorporated inquiry-based and place-based teaching methods. The course implementation can be summarized as follows: first, PBE inquiry instruction was provided for 14 weeks to enable preservice teachers to develop a comprehensive understanding of the environment, culture, and place-based characteristics of rural schools. Second, while teaching, preservice teachers were encouraged to apply their prior knowledge gained from daily life experiences and integrate it into natural science inquiry courses. Using this approach, the teachers increased their understanding and appreciation of the natural environment and cultural characteristics specific to rural areas and developed professional knowledge as teachers. For example, when designing teaching activities for ninth-grade students at a rural Bunun school on the topic of "torque and rotational motion," preservice teachers used hunting traps used by locals, including foot-binding traps and stone traps, as illustrative examples. They also applied the stages of 5E inquiry instruction to guide students through inquiry activities that would deepen students' understanding of place-based characteristics, highlight the significance of hunting, and showcase the wisdom of the elders of the area. The main research tool used in this study was the Teacher Professional Knowledge Scale questionnaire, which consists of three subscales: acquisition of professional knowledge, application of professional knowledge, and importance of professional knowledge. The questionnaire was administered to the preservice teachers in the first and last weeks of the semester. Qualitative data analysis was also performed. Reflective teaching journals, video and audio recordings of teaching activities, teacher reflections on teaching practices, end-of-term portfolios, and counseling records were obtained to collect qualitative data. The participants exhibited significant improvements in overall scores and in scores across the acquisition, application, and importance subscales. The participants also exhibited improvements in their ability to design and implement inquiry-based courses with rural PBE characteristics and in their ability to effectively participate in group learning, inquiry guidance, and questioning. Furthermore, the participants demonstrated an increased sense of responsibility toward rural students. In summary, by designing and implementing a PBE inquiry-based teaching course, preservice teachers learned how to effectively design and teach an inquiry-based course and gained valuable skills for facilitating group cooperative learning, developing effective questioning techniques for inquiry-based course design, and prioritizing student-centered teaching approaches. Furthermore, by incorporating PBE principles, the participants learned how to integrate the life experiences and local culture of rural students into their lessons, thereby increasing engagement among students. The participants also improved their understanding of science concepts, enhanced their professional competence and development focus, and developed a greater enthusiasm for rural education. These findings can be used as a reference for preservice teacher training courses.